2010
DOI: 10.1016/j.esas.2009.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of dysphagia comparing cervical arthroplasty and ACDF

Abstract: Study designRetrospective cohort from randomized prospective clinical trial.ObjectiveEvaluate incidence of dysphagia between instrumented ACDF and a no-profile cervical disc arthroplasty.Summary of background dataDysphagia is a well-known complication following anterior cervical discectomy and fusion (ACDF) and the etiology is multifactorial. One potential source for postoperative dysphagia involves the anterior profile of the implant used. Hence, a no-profile cervical disc arthroplasty could theoretically hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 16 publications
(21 reference statements)
1
31
0
Order By: Relevance
“…Furthermore, it has been hypothesized that the decrease in motion caused by ACDF can lead to the formation of more scar tissue than that caused by CDR and also can potentially contribute to swallowing difficulty. 27 In line with this hypothesis, it has been suggested that dysphagia increases the risk of aspiration and pneumonia. 4 Nonetheless, the higher morbidity rate after ACDF is most likely multifactorial and cannot be attributable to the subtle differences in the respective procedures alone.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, it has been hypothesized that the decrease in motion caused by ACDF can lead to the formation of more scar tissue than that caused by CDR and also can potentially contribute to swallowing difficulty. 27 In line with this hypothesis, it has been suggested that dysphagia increases the risk of aspiration and pneumonia. 4 Nonetheless, the higher morbidity rate after ACDF is most likely multifactorial and cannot be attributable to the subtle differences in the respective procedures alone.…”
Section: Discussionmentioning
confidence: 76%
“…22 We have noticed that a number of patients who undergo extension during ACDF complain of postoperative muscle spasms that generally subside within 6-8 weeks. Second, the instrumentation techniques used in ACDF need to be considered; the use of plates in ACDF has been linked to the development of dysphagia, 27 which was the cause of readmission for several patients who underwent this procedure in our study. Furthermore, it has been hypothesized that the decrease in motion caused by ACDF can lead to the formation of more scar tissue than that caused by CDR and also can potentially contribute to swallowing difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…The full text was assessed in the remaining 53 studies for eligibility criteria. Eventually, 10 published RCTs were included in the meta-analysis [11][12][13][17][18][19][20][21][22][23].…”
Section: Search Resultsmentioning
confidence: 99%
“…The CDA group received disc prosthesis and the ACDF group underwent interbody fusion with plate fixation. Eight of 10 studies were conducted in the United States and were multicenter FDA-regulated investigational device exemption pivotal trials [11][12][13]17,[19][20][21]23], and other studies were conducted in China [18] and Sweden [22]. Only 4 of 10 studies described the evaluation methods of dysphagia, including the Bazaz Dysphagia Score [11,12], Functional Outcome Swallowing Scale (FOSS) [21] and DSQ [22].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation